Brand Image and Price Influence BYD Purchase Intention through Green Lifestyle - Jonatan Sumana; Justin Kwannaka (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2026)
As the government promotes sustainable mobility and environmental consciousness, Indonesia's developing electric vehicle (EV) market demands a thorough knowledge of customer buying intention. This research uses consumer behaviour theory and the Theory of Planned Behaviour framework to examine how brand image and perceived price affect Build Your Dream electric car purchase intention, using green lifestyle as a mediating variable. Using a quantitative method and purposive selection of Jabodetabek respondents, Structural Equation Modeling–Partial Least Squares (SEM-PLS) was used to assess direct and indirect effects among factors. The results reveal that brand image and perceived price positively and significantly affect purchase intention. Furthermore, green lifestyle plays a significant mediating role, indicating that favourable brand perceptions and fair price evaluations strengthen environmentally oriented lifestyles and ultimately enhance consumers’ intention to purchase electric vehicles. These results emphasise the necessity of incorporating environmental values into marketing tactics to promote electric car adoption in Indonesia.